UAV-based rock mass characterization for geological strength index (GSI) assessment and comparison with conventional field mapping - Husaini, Ahmad Zharfan Ahmad; Rathinasamy, Vynotdni; Roslee, Mohamad Syazwan Mohd; Ismail, Mohd Ashraf Mohamad; Bhatawdekar, Ramesh Murlidhar; Hasbollah, Dayang Zulaika Abang; Suparmanto, Eka Kusmawati; Jialiang, Luo (International Conference “Environmental Engineering”, 2026)
Rock mass characterization is essential for reliable Geological Strength Index (GSI) estimation, particularly in inaccessible or steep slopes where conventional field mapping is challenging. This study evaluates the feasibility of utilizing Unmanned Aerial Vehicle (UAV)-based photogrammetry for GSI assessment using the Cai et al. (2004) chart in a granitic outcrop in Machang, Kelantan, Malaysia. Quantitative parameters, including block volume (Vb) and joint roughness, were derived from 3D point clouds, while joint condition factors (Jc) were assessed through both manual and UAV approaches. Results show strong correlation between UAV and manual assessments (R² = 0.9894 for GSI). The findings demonstrate that UAV-based methods can reliably replace conventional field mapping, improving safety, efficiency, and data density for GSI assessment of Cai et al. (2004).